An economical and environmentally friendly additive for chlorate decomposition process
By using coupling technology between alumina microsphere support and composite catalyst precursor in hypochlorite decomposition catalyst, the problem of nickel easy to fall off in the catalyst is solved, efficient fixation and reuse of the catalyst is achieved, and the decomposition efficiency and environmental protection of hypochlorite is improved.
Patent Information
- Application Number
- CN202411149086.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-08-21
AI Technical Summary
Among the existing hypochlorite decomposition catalysts, nickel has weak binding force with the support and is prone to fall off, resulting in insufficient reusability and environmental protection of the catalyst.
By using alumina microspheres as support, a rich pore structure is formed by phosphoric acid etching, and the composite catalyst precursor is coupled to the microspheres by sonication and coupling agent, and then the catalyst is carbonized and filled in the microspheres surface and pores through calcination to fix the catalyst.
The binding force between the catalyst and the support is improved, the catalyst falls off is reduced, the reusability and environmental protection of the catalyst is enhanced, and the decomposition efficiency of hypochlorite is improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to an economical and environmentally friendly additive for a chlorate decomposition process. Background Art
[0002] Sodium hypochlorite is a strong oxidant, deodorant and bleaching agent. It is widely used in the treatment of cyanide and foul-smelling sulfide wastewater, the decomposition of organic matter in wastewater, the control of microbial growth and mineral extraction. However, hypochlorite has a great impact on the environment. In some chemical processes, such as the chlor-alkali industry, hypochlorite will be discharged as a by-product. If it is not purified, it will cause harm to the environment. Although hypochlorite is unstable and easy to decompose, its decomposition rate is slow. Additives are needed to increase the decomposition rate of hypochlorite, so that hypochlorite can be decomposed into oxygen and sodium chloride that are harmless to the environment, reducing the harm of wastewater to the environment.
[0003] Patent CN114682262A discloses a hypochlorite decomposition catalyst, in which cerium is loaded on a carrier by an impregnation method, the carrier is then impregnated with a sodium hydroxide or potassium hydroxide solution, and then impregnated with a mixed solution of a cobalt salt, a nickel salt and hypochlorous acid to obtain a catalyst, cerium is used as an auxiliary agent to capture hypochlorite, and nickel and cobalt are used as active components to decompose hypochlorite, and the catalyst decomposition efficiency is high; however, the nickel in this scheme has a weak binding force with the carrier through the impregnation method, and may fall off in a wastewater solution containing sodium hypochlorite with strong oxidizing properties, and the nickel powder after falling off is difficult to remove, which is likely to cause new pollution. Summary of the invention
[0004] The purpose of the present invention is to provide an economical and environmentally friendly additive for chlorate decomposition process, so as to solve the problem that the catalyst in the additive has weak binding force with the carrier and is easy to fall off, so as to improve the reusability and environmental protection of the additive.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] An economical and environmentally friendly additive for chlorate decomposition process is prepared by the following steps:
[0007] Step 1: soak alumina microspheres with a particle size of 4-8 mm in a hydrochloric acid solution, wash, and electrolyze to remove the surface oxide film, then soak them in a 10wt% phosphoric acid solution for 20-30 minutes, and vacuum dry to obtain microporous alumina microspheres.
[0008] Step 2: Add the composite catalyst precursor and microporous alumina microspheres into sufficient deionized water in a reaction kettle, add octyltriethoxysilane, perform ultrasonic treatment at 300-500W for 20-30min, then filter and vacuum dry to obtain catalyst precursor microspheres.
[0009] Step 3: Place the catalyst precursor microspheres in a muffle furnace, heat to 140-150°C for preheating for 1-2 hours, then heat to 550-600°C at a rate of 5°C / min and calcine for 6-8 hours, and polish the surface of the obtained product to obtain the additive.
[0010] Further, the composite catalyst precursor is prepared by the following steps:
[0011] Ethylene glycol, ammonia water, sodium carbonate solution and aluminum nitrate solution are stirred and dissolved in a reaction kettle, and then a catalyst precursor is added, and the pH is adjusted to 8-8.5 with a sodium hydroxide solution, and the mixture is reacted in an oven at 140-150° C. for 20-24 hours, and then washed with deionized water and vacuum dried to constant weight to obtain a composite catalyst precursor.
[0012] Furthermore, the usage ratio of ethylene glycol, ammonia water, sodium carbonate solution, aluminum nitrate solution and catalyst precursor is 20-30 mL: 30-40 mL: 20-30 mL: 15-20 mL: 4-6 g.
[0013] Further, the concentration of the sodium carbonate solution is 1M, and the concentration of the aluminum nitrate solution is 2M.
[0014] Further, the catalyst precursor is prepared by the following steps:
[0015] Dissolve ferric nitrate nonahydrate and nickel nitrate hexahydrate in DMF in a beaker, add 2-aminoterephthalic acid, stir and ultrasonicate for 10-20 minutes, then place the solution in a hydrothermal autoclave, heat to 180-200°C and react for 10-12 hours. After the reaction is completed, centrifuge and wash the precipitate with ethanol and deionized water in turn to obtain a catalyst precursor.
[0016] Furthermore, the usage ratio of ferric nitrate nonahydrate, nickel nitrate hexahydrate, DMF and 2-aminoterephthalic acid is 2.5-3.5 g: 3-4.5 g: 60-90 mL: 1.2-1.5 g.
[0017] Furthermore, in step 1, the electrolyte of the electrolytic cell is 0.5M oxalic acid solution, and the voltage is 45V.
[0018] Furthermore, in step 2, the usage ratio of the composite catalyst precursor, microporous alumina microspheres and octyltriethoxysilane is 4-6g: 500-600g: 0.5-1g.
[0019] Beneficial effects of the present invention:
[0020] (1) The additive prepared by the present invention uses alumina microspheres as carriers, and has a rich, easily bonded pore structure after being etched with phosphoric acid. The composite catalyst precursor is coupled to the alumina microspheres through a silane coupling agent, and then the composite catalyst precursor is carbonized and filled on the surface and pores of the alumina microspheres through a calcination treatment. The expansion force generated by the carbonization firmly fixes the catalyst on the surface of the alumina microspheres, so that the catalyst in the prepared additive has a strong ability to bind to the carrier, is not easy to fall off, has a good catalytic effect, is highly reusable, and is economical and environmentally friendly.
[0021] (2) The additive prepared by the present invention is used to prepare a catalyst precursor by using iron and nickel elements. Under the action of roasting, a composite structure of iron oxide and nickel trioxide is generated. The iron oxide accelerates the conversion of nickel elements between different valence states, improves the oxidation capacity of the active sites of the nickel-based catalyst, and thus improves the catalytic efficiency of nickel trioxide on hypochlorite.
[0022] (3) The porous carbon structure produced by carbonization in the additive prepared by the present invention provides high porosity and large specific surface area, and has abundant active sites. In addition, the aluminum hydroxide precipitated in the composite catalyst precursor will become aluminum oxide and fuse with the microporous alumina microspheres during the roasting process, thereby producing a fixing effect, firmly fixing the expanded carbon structure in the pores and surface of the microporous alumina microspheres. After surface polishing, the carbon structure with low bonding degree is removed, and the carbon structure in the pores of the microporous alumina microspheres is retained, thereby improving the service life and circulation capacity of the catalyst. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1: An economical and environmentally friendly additive for chlorate decomposition process, prepared by the following steps:
[0025] Step 1: Soak alumina microspheres with a particle size of 4 mm in a 0.5 M hydrochloric acid solution for 12 hours to remove the surface oxide film, wash them with ethanol and deionized water in turn, and then oxidize them in an electrolytic cell for 2 hours. The electrolyte is a 0.5 M oxalic acid solution and the voltage is 45 V. Then, soak the oxidized alumina microspheres in a 10 wt % phosphoric acid solution for 20 minutes. After vacuum drying, microporous alumina microspheres are obtained.
[0026] Step 2: Dissolve 2.5 g of ferric nitrate nonahydrate and 3 g of nickel nitrate hexahydrate in 60 mL of DMF in a beaker, add 1.2 g of 2-aminoterephthalic acid, stir and ultrasonicate for 10 min, then place the solution in a hydrothermal autoclave, heat to 180 ° C and react for 10 h. After the reaction is completed, centrifuge and wash the precipitate with ethanol and deionized water in turn to obtain a catalyst precursor.
[0027] Step 3: Stir and dissolve 20 mL of ethylene glycol, 30 mL of ammonia water, 20 mL of 1 M sodium carbonate solution and 15 mL of 2 M aluminum nitrate solution in a reactor, then add 4 g of catalyst precursor, adjust the pH to 8 with 0.1 M sodium hydroxide solution, react in an oven at 140°C for 20 hours, then wash with deionized water and vacuum dry to constant weight to obtain a composite catalyst precursor.
[0028] Step 4: Add 4 g of the composite catalyst precursor and 500 g of microporous alumina microspheres into sufficient deionized water in a reaction kettle, add 0.5 g of octyltriethoxysilane, perform ultrasonic treatment at 300 W for 20 min, then filter and vacuum dry to obtain catalyst precursor microspheres.
[0029] Step 5: Place the catalyst precursor microspheres in a muffle furnace, heat to 140°C for preheating for 1 hour, then heat to 550°C at a rate of 5°C / min and calcine for 6 hours. Polish the surface of the obtained product to obtain the additive.
[0030] Example 2: An economical and environmentally friendly additive for chlorate decomposition process, prepared by the following steps:
[0031] Step 1: Soak the alumina microspheres with a particle size of 6 mm in a 0.5 M hydrochloric acid solution for 15 hours to remove the surface oxide film, wash them with ethanol and deionized water in turn, and then oxidize them in an electrolytic cell for 2.5 hours. The electrolyte is a 0.5 M oxalic acid solution and the voltage is 45 V. Then, soak the oxidized alumina microspheres in a 10 wt % phosphoric acid solution for 25 minutes. After vacuum drying, microporous alumina microspheres are obtained.
[0032] Step 2: Dissolve 3 g of ferric nitrate nonahydrate and 4 g of nickel nitrate hexahydrate in 75 mL of DMF in a beaker, add 1.35 g of 2-aminoterephthalic acid, stir and ultrasonicate for 15 min, then place the solution in a hydrothermal autoclave, heat to 190 ° C and react for 11 h. After the reaction is completed, centrifuge and wash the precipitate with ethanol and deionized water in turn to obtain a catalyst precursor.
[0033] Step 3: Stir and dissolve 25 mL of ethylene glycol, 35 mL of ammonia water, 25 mL of 1 M sodium carbonate solution and 17 mL of 2 M aluminum nitrate solution in a reactor, then add 5 g of catalyst precursor, adjust the pH to 8.2 with 0.1 M sodium hydroxide solution, react in an oven at 145°C for 22 hours, then wash with deionized water and vacuum dry to constant weight to obtain a composite catalyst precursor.
[0034] Step 4: Add 5 g of the composite catalyst precursor and 550 g of microporous alumina microspheres into sufficient deionized water in a reaction kettle, add 0.75 g of octyltriethoxysilane, perform ultrasonic treatment at 400 W for 25 min, then filter and vacuum dry to obtain catalyst precursor microspheres.
[0035] Step 5: Place the catalyst precursor microspheres in a muffle furnace, heat to 145°C for preheating for 1.5 hours, then heat to 575°C at a rate of 5°C / min and calcine for 7 hours. Polish the surface of the obtained product to obtain the additive.
[0036] Example 3: An economical and environmentally friendly additive for chlorate decomposition process, prepared by the following steps:
[0037] Step 1: Soak the alumina microspheres with a particle size of 8 mm in a 0.5 M hydrochloric acid solution for 18 hours to remove the surface oxide film, wash them with ethanol and deionized water in turn, and then oxidize them in an electrolytic cell for 3 hours. The electrolyte is a 0.5 M oxalic acid solution and the voltage is 45 V. Then, soak the oxidized alumina microspheres in a 10 wt % phosphoric acid solution for 30 minutes. After vacuum drying, microporous alumina microspheres are obtained.
[0038] Step 2: Dissolve 3.5 g of ferric nitrate nonahydrate and 4.5 g of nickel nitrate hexahydrate in 90 mL of DMF in a beaker, add 1.5 g of 2-aminoterephthalic acid, stir and ultrasonicate for 20 min, then place the solution in a hydrothermal autoclave, heat to 200 ° C and react for 12 h. After the reaction is completed, centrifuge and wash the precipitate with ethanol and deionized water in turn to obtain a catalyst precursor.
[0039] Step 3: Stir and dissolve 30 mL of ethylene glycol, 40 mL of ammonia water, 30 mL of 1 M sodium carbonate solution and 20 mL of 2 M aluminum nitrate solution in a reactor, then add 6 g of catalyst precursor, adjust the pH to 8.5 with 0.1 M sodium hydroxide solution, react in an oven at 150°C for 24 hours, then wash with deionized water and vacuum dry to constant weight to obtain a composite catalyst precursor.
[0040] Step 4: Add 6 g of the composite catalyst precursor and 600 g of microporous alumina microspheres into sufficient deionized water in a reaction kettle, add 1 g of octyltriethoxysilane, perform ultrasonic treatment at 500 W for 30 min, then filter and vacuum dry to obtain catalyst precursor microspheres.
[0041] Step 5: Place the catalyst precursor microspheres in a muffle furnace, heat to 150° C. and preheat for 2 h, then heat to 600° C. at a rate of 5° C. / min and calcine for 8 h, and polish the surface of the obtained product to obtain the additive.
[0042] Principle of the invention:
[0043] The stains on the surface of the alumina microspheres are removed by soaking in hydrochloric acid, and then the oxide film on the surface of the alumina microspheres is removed by oxidation in an electrolytic cell, the acid etching effect of the phosphoric acid solution on the surface of the alumina microspheres is increased, and the number and pore area of the pores on the surface of the alumina microspheres are increased; the two metals of iron and nickel are mixed to prepare a catalyst precursor, and the catalyst precursor has a rich porous structure, which can make the aluminum hydroxide precipitate generated by aluminum nitrate generated in the pore structure of the catalyst precursor to form a composite catalyst precursor, and the composite catalyst precursor is coupled to the surface and pores of the microporous alumina microspheres through the coupling effect of octyltriethoxysilane. Under high-temperature calcination, the 2-aminoterephthalic acid in the catalyst precursor will carbonize and expand, and the expanded carbon will fill the pores of the microporous alumina microspheres to form a porous carbon structure. At the same time, the iron and nickel metals will be oxidized into iron oxide and nickel trioxide. Nickel trioxide has a significant catalytic effect on the decomposition of hypochlorite, which can improve the decomposition efficiency of hypochlorite, and iron oxide can accelerate the reaction between different valence states of nickel elements. The conversion improves the oxidation capacity of the active sites of the nickel-based catalyst, thereby improving the catalytic efficiency of nickel trioxide; the porous carbon structure has high porosity and large specific surface area, has abundant active sites, and is easy to transfer mass; during the calcination process, the aluminum hydroxide in the pore structure of the catalyst precursor will become aluminum oxide and fuse with the microporous alumina microspheres, thereby producing a fixing effect, firmly fixing the expanded carbon structure in the pores and surface of the microporous alumina microspheres, and improving the service life and circulation capacity of the catalyst; due to the coupling effect of the coupling agent, part of the composite catalyst precursor will adhere to the surface of the microporous alumina microspheres, and the catalyst carbonization layer formed after the carbonization of the composite catalyst precursor attached to the surface has a weaker bonding force with the microporous alumina microspheres than the catalyst carbonization layer formed in the pores, and the carbonization layer in the pores will also partially expand beyond the pores, so the catalyst carbon layer with poor surface bonding force of the additive is removed by slight surface grinding, reducing the falling off of the catalyst carbon layer caused by collision during the decomposition of hypochlorite by the additive, thereby causing new pollution.
[0044] Comparative Example 1: The microporous alumina microspheres were immersed in a 1 M nickel nitrate hexahydrate solution, dried at 80° C. for 12 h, and then calcined at 500° C. for 6 h to obtain an additive.
[0045] Comparative Example 2: The difference from Example 1 is that ferric nitrate nonahydrate is not added in step 2.
[0046] Comparative Example 3: The difference from Example 1 is that in step 4, a catalyst precursor is used instead of a composite catalyst precursor.
[0047] The sources of some reagents in the embodiments and comparative examples are as follows:
[0048] Octyltriethoxysilane and 2-aminoterephthalic acid were purchased from MacLean Reagent Co., Ltd.
[0049] Ferric nitrate nonahydrate, nickel nitrate hexahydrate, aluminum nitrate nonahydrate and DMF were all purchased from Sigma-Aldrich.
[0050] Alumina microspheres were purchased from Henan Taihang Water Purification Materials Co., Ltd.
[0051] The performance test of the additives prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was carried out. In the experiment, 400 g of the catalyst was filled into a column with a diameter of 4 cm and a height of 50 cm. A 2.5% sodium hypochlorite solution was passed into the column. A U-shaped tube was connected to the top of the column. The residence time was controlled to be 20 min and the reaction temperature was 60° C. The catalytic sodium hypochlorite decomposition experiment was carried out. The decomposition rate of the sodium hypochlorite solution was calculated according to the speed of the liquid level rising in the U-shaped tube; the additives prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were continuously flushed in the column at a flow rate of 1.0 m / s for 15 days, and weighed after drying to calculate the weight loss rate of the additives. The results are shown in Table 1:
[0052] Table 1
[0053] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Decomposition rate % 98.82 99.17 99.23 68.51 81.35 97.64 Weight loss rate % 0.047 0.052 0.055 0.138 0.057 0.069
[0054] As can be seen from Table 1, the additives prepared in Examples 1 to 3 of the present invention have a good effect on promoting the decomposition of hypochlorite, indicating that the catalyst carbon layer of the present invention has a rich porous structure, rich active sites, and high catalytic efficiency; in Comparative Example 1, the nickel oxide is easy to fall off due to the impregnation and calcination method, and the porous structure is small, the contact area with hypochlorite is small, and the catalytic efficiency is low; Comparative Example 2 does not contain iron and cannot oxidize iron to promote the catalytic effect of nickel, so the decomposition rate is low; Comparative Example 3 does not have the reinforcement effect of aluminum oxide, and the catalyst carbon layer partially falls off, resulting in a catalytic efficiency slightly lower than that of Examples 1 to 3.
[0055] The weight loss rates of Examples 1 to 3 of the present invention under continuous water flow impact are low, indicating that the catalyst carbon layer of the present invention has a strong bonding force with the alumina microsphere carrier and is not easy to fall off. In Comparative Example 1, since the nickel oxide bonding force is weak and easy to fall off after direct impregnation and calcination, the weight loss rate is high; in Comparative Example 3, since the catalyst carbon layer does not contain aluminum hydroxide precipitate, the bonding force with the alumina microsphere carrier is weaker than that of Examples 1 to 3, the weight loss rate is higher than that of Examples 1 to 3.
[0056] It should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0057] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An economical and environmentally friendly additive for chlorate decomposition process, characterized in that: Prepared by the following steps: Step 1: soak alumina microspheres with a particle size of 4-8 mm in a hydrochloric acid solution, wash, and electrolyze to remove the surface oxide film, then soak them in a 10wt% phosphoric acid solution for 20-30 minutes, and vacuum dry to obtain microporous alumina microspheres; Step 2: Add the composite catalyst precursor and microporous alumina microspheres into sufficient deionized water in a reaction kettle, add octyltriethoxysilane, perform ultrasonic treatment at 300-500W for 20-30min, then filter and vacuum dry to obtain catalyst precursor microspheres; Step 3: Place the catalyst precursor microspheres in a muffle furnace, heat to 140-150°C for preheating for 1-2 hours, then heat to 550-600°C at a rate of 5°C / min and calcine for 6-8 hours, and polish the surface of the obtained product to obtain the additive; The composite catalyst precursor is prepared by the following steps: Stir and dissolve ethylene glycol, ammonia water, sodium carbonate solution and aluminum nitrate solution in a reaction kettle, then add a catalyst precursor, adjust the pH to 8-8.5 with a sodium hydroxide solution, react in an oven at 140-150° C. for 20-24 hours, then wash with deionized water, and vacuum dry to constant weight to obtain a composite catalyst precursor; The catalyst precursor is prepared by the following steps: Dissolve ferric nitrate nonahydrate and nickel nitrate hexahydrate in DMF in a beaker, add 2-aminoterephthalic acid, stir and ultrasonicate for 10-20 minutes, then place the solution in a hydrothermal autoclave, heat to 180-200°C and react for 10-12 hours. After the reaction is completed, centrifuge and wash the precipitate with ethanol and deionized water in turn to obtain a catalyst precursor.
2. An economical and environmentally friendly additive for chlorate decomposition process according to claim 1, characterized in that: The usage ratio of the ethylene glycol, ammonia water, sodium carbonate solution, aluminum nitrate solution and catalyst precursor is 20-30 mL: 30-40 mL: 20-30 mL: 15-20 mL: 4-6 g.
3. An economical and environmentally friendly additive for chlorate decomposition process according to claim 2, characterized in that: The concentration of the sodium carbonate solution is 1M, and the concentration of the aluminum nitrate solution is 2M.
4. The economical and environmentally friendly additive for chlorate decomposition process according to claim 1, characterized in that: The usage ratio of the ferric nitrate nonahydrate, nickel nitrate hexahydrate, DMF and 2-aminoterephthalic acid is 2.5-3.5 g: 3-4.5 g: 60-90 mL: 1.2-1.5 g.
5. The economical and environmentally friendly additive for chlorate decomposition process according to claim 1, characterized in that: The electrolyte of the electrolytic cell in step 1 is 0.5M oxalic acid solution, and the voltage is 45V.
6. The economical and environmentally friendly additive for chlorate decomposition process according to claim 1, characterized in that: The usage ratio of the composite catalyst precursor, microporous alumina microspheres and octyltriethoxysilane in step 2 is 4-6g: 500-600g: 0.5-1g.
Citation Information
Patent Citations
Fischer-Tropsch Catalyst Based On A Group Viiib Metal And A Carrier Of Oxides Including Alumina, Silica, A Spinel And Phosphorus
CN104923270A
Preparation method of core-shell structure loaded catalyst
CN110227537A